Development of project based learning tool using PLC trainer to improve creativity and self-reliance - Elsanda Merita Indrawati; Kuni Nadliroh (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This research aims to analyze: (1) quality of project based learning tool with trainer PLC, (2) the creativity of students after following the learning to use project based learning tool with trainer PLC, and (3) self-reliance learn student after following learning using project based learning tools with trainer PLC. This research is a research and development (R&D) using One Group Pretest Postest Design. The results showed that (1) the learning tools of project based learning with PLC trainer shows excellent quality with a score of 81.4%; (2) the creativity of students after implementing learning using learning tools of project based learning with PLS trainer has increased with the average value of N-gain of 0.60 criteria medium; (3) the self-reliance of the student learning increased after implementing learning using project based learning tools with PLC trainer, indicated by the average value of N-gain of 0.55 with medium criteria.